Board Game Komunikasi Visual Kampanye Love Language pada Pasangan Suami Istri di Kota Palembang - Fajri, Ahmad Istiqlal; Bobby Halim; Yosef Yulius (UNIVERSITAS INDO GLOBAL MANDIRI, 2024)
Love language, basically, is the language of love in the form of actions, behavior and attitudes that make someone feel appreciated and loved. Love language has five forms, namely words of affirmation, quality time, receiving gifts, acts of service, physical touch. This campaign uses board games as the main medium for conveying information and education with interesting media. The main idea in developing this media is a folk tale from Central Java, namely Joko Kendil. This story has a message about true love, patience, and sacrifice of a husband and wife in facing trials in life. The aim of this love language campaign is to reduce the risk of disputes and maintain household harmony. The method used in this design is Design Thinking which consists of 5 stages, namely Empathize (understanding the problem), Define (analyzing data), Ideate (generating an idea or concept), Prototype (visualizing the idea), Test (testimonial to the target audience). As a result of testimonials to the target audience, positive feedback was obtained where the target audience was attracted through the colorful visual campaign media and helped in understanding their language through interesting and enjoyable verbal messages. Keyword : Love Language, Board Game, Married Couple.